The mature phyllosphere microbiome of grapevine is associated with resistance against Plasmopara viticola - Wicaksono, Wisnu Adi; Morauf, Christina; Müller, Henry; Abdelfattah, Ahmed; Donat, Christina; Berg, Gabriele (Frontiers in Microbiology, 2023)
Phyllosphere microbiota represents a substantial but hardly explored reservoir for disease resistance mechanisms. The goal of our study was to understand the link between grapevine cultivars susceptibility to Plasmopara viticola, one of the most devastating leaf pathogens in viticulture, and the phyllosphere microbiota. Therefore, we analyzed a 16S rRNA gene library for the dominant phyllosphere bacterial phyla Alphaproteobacteria of seven Vitis genotypes at different developmental stages, i.e., flowering and harvesting, via amplicon sequencing. Young leaves had significantly higher Alphaproteobacterial richness and diversity without significant host-specificity. In contrast, the microbial communities of mature leaves were structurally distinct in accordance with P. viticola resistance levels. This statistically significant link between mature bacterial phyllosphere communities and resistant phenotypes was corroborated by beta diversity metrics and network analysis. Beyond direct host-driven effects via the provision of microhabitats, we found evidence that plants recruit for specific bacterial taxa that were likely playing a fundamental role in mediating microbe-microbe interactions and structuring clusters within mature communities. Our results on grape-microbiota interaction provide insights for targeted biocontrol and breeding strategies.